The Anti-inflammatory Effect of Soluble Epoxide Hydrolase Inhibitor and 14, 15-EET in Kawasaki Disease Through PPARγ/STAT1 Signaling Pathway - Dai, Na; Yang, Chunyan; Fan, Qing; Wang, Minmin; Liu, Xiaoyue; Zhao, Haizhao; Zhao, Cuifen (Frontiers in Pediatrics, 2020)
Soluble epoxide hydrolase (sEH) is responsible for rapid degradation of 14, 15-EET, which is one of the isomers of EETs and plays an important role in cardiovascular diseases. In this study, we investigated the mechanism by which sEH inhibitor AUDA played an anti-inflammatory effect in HCAECs. Our results indicated that AUDA treatment promoted PPARγ expression, while knockdown of PPARγ blocked the cell growth and STAT1 expression inhibition induced by 100 μmol/L AUDA in HCAECs. AUDA also inhibited the overexpression of TNF - α, IL-1 β and MMP-9 induced by KD sera in HCAECs. Moreover, 30 blood samples from children with Kawasaki disease (KD) were collected with 30 healthy children as the control group. QPCR and ELISA assays were used to detect the level of 14, 15-EET, TNF-α, IL-1 and MMP-9. We found that the level of 14, 15-EET was higher in peripheral blood of children with KD compared with healthy controls (P<0.05). In comparison to KD children with non-coronary artery lesion (nCAL), the level of 14, 15-EET was higher in peripheral blood of KD children with coronary artery lesion (CAL) (P<0.05). Compared with healthy control group, the expression levels of TNF-α, IL-1 and MMP-9 in patients with KD were significantly up-regulated. Compared with nCAL KD children, the expression levels of TNF-α, IL-1 and MMP-9 in CAL children were abnormally high (P<0.05). Our study indicated that AUDA played an anti-inflammatory effect in HCAECs through PPARγ/STAT1 signaling pathway, and 14, 15-EET is up-regulated in children with KD, suggesting that 14, 15-EET involved in the progression of KD.